REGULATORY CONSIDERATIONS OF MIGRATION FLOWS WITHIN THE FRAMEWORK OF EU-15 AND COMMON MIGRATION POLICY OF EUROPEAN UNION - Markovska, Halyna (Journal of European Economy, 2017)
The regulatory considerations of migration flows within the framework ofEU-15 are considered. The institutional levels of migration management in the EU member states are analyzed and the division of national migration policy of EU member states within the framework of internal migration flows of EU member states and towards the migrants from the Third World countries is offered.